2011
DOI: 10.1371/journal.pone.0021574
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Epidermal Growth Factor Receptor Signaling during Luteinizing Hormone-Induced Oocyte Maturation

Abstract: Recent evidence that luteinizing hormone (LH) stimulation of ovulatory follicles causes transactivation of the epidermal growth factor receptor (EGFR) has provided insights into the mechanisms of ovulation. However, the complete array of signals that promote oocyte reentry into the meiotic cell cycle in the follicle are still incompletely understood. To elucidate the signaling downstream of EGFR involved in oocyte maturation, we have investigated the LH responses in granulosa cells with targeted ablation of EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 44 publications
6
83
0
Order By: Relevance
“…Lhcgr encodes the LH receptor that is required for ovulation, cumulus cell expansion, and the resumption of meiosis (67); Cyp11a1 encodes cytochrome P450 side chain cleavage, the rate-limiting enzyme for progesterone biosynthesis (18,68); the EGFR contributes to LH-stimulated expansion of cumulus granulosa cells, resumption of meiosis, and ovulation (27,69,70); Cyp19a1 encodes aromatase, the rate-limiting enzyme in estrogen biosynthesis (71); Inha encodes for the inhibin hormone subunit inhibin-␣ that inhibits FSH expression by the anterior pituitary (72); Hsd17b1 encodes the enzyme that converts androstenedione and estrone to testosterone and estradiol-17␤, respectively, and is required for normal ovulation and corpus luteum formation (73); and Pappa encodes a secreted metalloproteinase that cleaves IGF-binding proteins and contributes to estrogen and progesterone biosynthesis and to ovulation (74).…”
Section: Discussionmentioning
confidence: 99%
“…Lhcgr encodes the LH receptor that is required for ovulation, cumulus cell expansion, and the resumption of meiosis (67); Cyp11a1 encodes cytochrome P450 side chain cleavage, the rate-limiting enzyme for progesterone biosynthesis (18,68); the EGFR contributes to LH-stimulated expansion of cumulus granulosa cells, resumption of meiosis, and ovulation (27,69,70); Cyp19a1 encodes aromatase, the rate-limiting enzyme in estrogen biosynthesis (71); Inha encodes for the inhibin hormone subunit inhibin-␣ that inhibits FSH expression by the anterior pituitary (72); Hsd17b1 encodes the enzyme that converts androstenedione and estrone to testosterone and estradiol-17␤, respectively, and is required for normal ovulation and corpus luteum formation (73); and Pappa encodes a secreted metalloproteinase that cleaves IGF-binding proteins and contributes to estrogen and progesterone biosynthesis and to ovulation (74).…”
Section: Discussionmentioning
confidence: 99%
“…The drop in the intercellular communication is necessary for meiosis reinitiation and is supposed to limit transfer of meiosis blocking substances to the oocyte. In the mouse, activation of EGFR is involved in LH-induced decrease in cGMP transport from granulosa and cumulus cells to the oocyte and both EGFR and MAPK3/1 activities participate in gap junction closure (Vaccari et al 2009, Norris et al 2009, Hsieh et al 2011. These mechanisms contribute to relieve meiotic block as cGMP works in oocytes as a natural inhibitor of phosphodiesterase 3A, maintaining high intracellular level of cAMP and meiotic arrest of the oocyte (Masciarelli et al 2004).…”
Section: Signaling In Pig Cumulus-oocyte Complexesmentioning
confidence: 99%
“…However, recent studies have shown that FSH signaling in granulosa and also in cumulus cells is more complex and some molecular events occur even independently of PKA activation through cAMP-activated exchange factor pathway (Wayne et al 2007). The gonadotropin-induced production of EGF-like peptides leads to a transactivation of EGF receptor (EGFR; Conti et al 2006) as these peptides bind to a classical EGFR (ERBB1), activate its intrinsic tyrosine kinase, and downstream signaling cascades, including MAPK3/1, MAPK14, and phosphoinositide-3-kinase/v-akt murine thymoma viral oncogene homolog (PI3K/AKT) pathways (Shimada et al 2006, Hsieh et al 2011. Therefore, gonadotropins activate a broad signaling network in cultured COCs, which results in essential changes in transcription profiling in the cumulus cells and consequently in series of posttranscriptional molecular events in the oocytes leading to the resumption of meiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, FSH increases glucose uptake (Roberts et al, 2004), as well as promotes glycolysis and PPP in the mouse (Downs & Utecht, 1999), and augment TCA in the cow (Zuelke & Brackett, 1992). Luteinizing hormone surge (LH) plays significant roles in meiotic maturation of mammalian oocytes (Gougeon, 2010;Son et al, 2011, Hsieh et al, 2011. LH surge causes a significant decline in gap junctions leading to dissociation of granulosa cells from the gamete and expansion of the cumulus cells.…”
Section: Glucose Is a Key Substrate For Providing Energy During Oocytmentioning
confidence: 99%
“…LH surge causes a significant decline in gap junctions leading to dissociation of granulosa cells from the gamete and expansion of the cumulus cells. LH also activates its G-protein-coupled receptor on theca and granulosa cells, which in turn leads to elevation of intracellular cAMP that subsequently triggers multiple downstream pathways regulating meiotic maturation and ovulation (Hsieh et al, 2011, Sun et al, 2009). Finally, LH promotes cow oocytes maturation by modifying gamete's nutritional microenvironment via increasing glucose utilization through glycolysis and TCA cycle (Zuelke & Brackett, 1992).…”
Section: Glucose Is a Key Substrate For Providing Energy During Oocytmentioning
confidence: 99%